Comparison of the Effect of Propranolol Combination with Cinnarizine and Propranolol in the Prevention of Acute Migraine Attacks: Propranolol effect on Acute Migraine Attacks - Adeeb Sheet, Dereen; Bibani, Rashid Hamid; Kheder, Azad Hasan (Cellular and Molecular Biology, 2022)
Acute migraine attacks disrupt performance and reduce the quality of life. Therefore, efforts to prevent these attacks continue using different medications. This study aimed to compare the effect of cinnarizine combination with propranolol and propranolol with placebo in preventing acute migraine attacks. This study was a semi-experimental study performed on 120 adult patients with migraine referred to Department of Neurology in Rezgary Teaching Hospital in Erbil.. Participants were randomly allocated to two groups control (propranolol) and intervention (propranolol with cinnarizine). The frequency, duration and severity of headache attacks were recorded and followed within two months. Data were analyzed with SPSS ver23 software and T-paired, independent T-tests and ANOVA. The average age of the participants was 34.54 years. 60% were female and 55% had a family history of migraine. The average frequency of headache attacks in the intervention group decreased by 75 % (from 15 times to 3 times) and a 50 % decrease in the control group (from 12 times to 6 times). The duration and severity of headaches in both intervention and control groups decreased (p <0.001), respectively. The average frequency, duration and severity of headache attacks in the first- and second months during treatment in the intervention group and control group were statistically different (p <0.001). The drug combination of propranolol with cinnarizine has an additional effect on reducing acute migraine attacks compared to propranolol alone.